2000
DOI: 10.1001/archinte.160.2.152
|View full text |Cite
|
Sign up to set email alerts
|

St John's Wort for Depression

Abstract: T o address whether St John's wort is useful for the treatment of depression we attempted to retrieve all English-language articles with data on the efficacy, safety, and availability of St John's wort. Randomized, controlled, double-blind trials were selected and assessed for methodological quality using a standardized checklist, and data on pharmacology, cost, regulation, and safety were extracted. Eight studies were identified, found to be of generally good methodological quality, and determined to provide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
86
0
3

Year Published

2000
2000
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(90 citation statements)
references
References 32 publications
1
86
0
3
Order By: Relevance
“…Johnʼs wort (Hypericum perforatum) extract is used for insomnia and depression [113]. Flavonol glycosides are the major class of compounds found in St. Johnʼs wort extract, with rutin, hyperoside, isoquercitrin, quercitrin (quercetin 3-rhamnoside), and miquelianin being the main compounds.…”
Section: St Johnʼs Wortmentioning
confidence: 99%
“…Johnʼs wort (Hypericum perforatum) extract is used for insomnia and depression [113]. Flavonol glycosides are the major class of compounds found in St. Johnʼs wort extract, with rutin, hyperoside, isoquercitrin, quercitrin (quercetin 3-rhamnoside), and miquelianin being the main compounds.…”
Section: St Johnʼs Wortmentioning
confidence: 99%
“…In Germany, where extracts of the plant are licensed as a medication, St. John's wort or hypericum is used more extensively than et al 1996). Since the publication of that influential report, several other systematic reviews (and one metaanalysis) have appeared which further support the antidepressant efficacy of hypericum (Josey and Tackett 1999;Kim et al 1999;Stevinson and Ernst 1999;Gaster and Holroyd 2000). Furthermore, in comparison with other antidepressants, St. John's wort is well tolerated and has a low side effect profile (Linde et al 1996;Ernst et al 1998 Despite its widespread use, the active constituents and mechanism of antidepressant action of St. John's wort remain largely unknown (Bennett et al 1998;Nathan 1999).…”
Section: -Hydroxytryptamine (Serotonin); Electrophysiologymentioning
confidence: 98%
“…A widely cited meta-analysis of 23 randomized clinical trials concluded that hypericum extracts were significantly superior to placebo and comparable to tricyclic antidepressant drugs in alleviating depressive symptoms (Linde et al 1996). Since the publication of that influential report, several other systematic reviews (and one metaanalysis) have appeared which further support the antidepressant efficacy of hypericum (Josey and Tackett 1999;Kim et al 1999;Stevinson and Ernst 1999;Gaster and Holroyd 2000). Furthermore, in comparison with other antidepressants, St. John's wort is well tolerated and has a low side effect profile (Linde et al 1996;Ernst et al 1998).…”
mentioning
confidence: 99%
“…The ethnopharmacological uses and huge prescriptions of St.John's wort (Hypericum perforatum L) -best known as 'Nature's Prozac® (fluoxetine) 3 -established this herbal drug as natural antidepressant. All critical analysis on commercial and other information available on sales of herbal medicines in the USA shows that, for the first eight months of 1998, it ranked second to Ginko as the best selling herbal drug, with retail sales valued at over $200 million 4 .…”
Section: St John's Wort: Phytopharmacotherapy Of Depressionmentioning
confidence: 99%